A SYSTEMATIC APPROACH FOR INCREASING THE SUCCESS OF KITCHEN INTERIOR DESIGN WITHIN THE CONTEXT OF SPATIAL USER REQUIREMENTS - Yazıcıoğlu, Deniz Ayşe; Kanoğlu, Alaattin (Advances in Social Sciences Research Journal, 2016)
One of the most studied areas for increasing the performance of interior design is the kitchen. The reason for this is it’s being the most important area of work compared to other areas from which high performance in many criteria is expected such as functionality, durability and hygiene. As a result of the literature survey carried out within the purview of the study as to increasing the design performance it was found that scientific efforts for increasing the performance of kitchen design is divided into two groups. The first group consists of those germane to industrial kitchen products. Studies in the other group provide information as regards basic design rules for increasing the kitchen design performance. There was no study on establishing the relation between "basic design rules" and "user requirements" in a systematic way for increasing the kitchen design performance in these obtained resources. As such, the purpose of this study is establishment of a systematic classification in which a relational link between the design rules proposed for increasing the performance of kitchen design with user requirements in kitchen is created. The scope of the study is limited to only one of the user's requirements with an eye to reach more accurate results. In line with this identified scope and purpose, the methodology of the study is determined as which of the user requirements will be discussed in the first phase with the reasons thereof. Subsequently, a literature survey was conducted and the set of design rules for increasing the kitchen design success was created. A systematic classification in which the relational link has been established between the design rules and user requirements at the last phase.